Establishing a method to estimate the cost‐effectiveness of a kindergarten‐based, family‐involved intervention to prevent obesity in early childhood. The ToyBox‐study. (August 2014) - Pil, L.; Putman, K.; Cardon, G.; De Bourdeaudhuij, I.; Manios, Y.; Androutsos, O.; Lateva, M.; Iotova, V.; Zych, K.; Góźdź, M.; González‐Gil, E. M.; De Miguel‐Etayo, P.; et al.
Summary: Overweight and obesity in children are recognized as a major health problem. The ToyBox‐intervention was developed with the aim of preventing obesity in pre‐schoolers. Because it is increasingly important to inform policy makers not only on the effects of prevention interventions, but also on their costs and cost‐effectiveness, our purpose was to establish a method to estimate the cost‐effectiveness of the ToyBox‐intervention. In order to estimate the long‐term impact of the ToyBox‐intervention on health and societal costs, extrapolations of the intervention effect will be conducted to predict children's weight status (based on the body mass index) at adult age. Effects of the adult weight status on the prevalence of obesity‐related complications will be modelled through a Markov model, with a total time horizon of 70 years and a cycle length of 1 year. The model will be conducted in six European countries participating in the ToyBox‐intervention, based on country‐specific economic and epidemiological data. This study describes the methodological rationale and implementation of an analytic model to examine the cost‐effectiveness of the ToyBox‐intervention for six European countries, in order to inform decision‐makers on the value for money of this intervention in the prevention of obesity in pre‐schoolers.